A Photosensitive Polymeric Carrier with a Renewable Singlet Oxygen Reservoir Regulated by Two NIR Beams for Enhanced Antitumor Phototherapy. Issue 29 (18th June 2021) - Yang, Chun; Su, Meihui; Luo, Pei; Liu, Yanan; Yang, Feng; Li, Changhua
Abstract: Photodynamic therapy (PDT), which utilizes photosensitizer to convert molecular oxygen into singlet oxygen ( 1 O2 ) upon laser irradiation to ablate tumors, will exacerbate the already oxygen shortage of most solid tumors and is thus self‐limiting. Herein, a sophisticated photosensitive polymeric material (An‐NP) that allows sustained 1 O2 generation and sufficient oxygen supply during the entire phototherapy is engineered by alternatively applying PDT and photothermal therapy (PTT) controlled by two NIR laser beams. In addition to a photosensitizer that generates 1 O2, An‐NP consists of two other key components: a molecularly designed anthracene derivative capable of trapping/releasing 1 O2 with superior reversibility and a dye J‐aggregate with superb photothermal performance. Thus, in 655 nm laser‐triggered PDT process, An‐NP generates abundant 1 O2 with extra 1 O2 being trapped via the conversion into EPO‐NP; while in the subsequent 785 nm laser‐driven PTT process, the converted EPO‐NP undergoes thermolysis to liberate the captured 1 O2 and regenerates An‐NP. The intratumoral oxygen level can be replenished during the PTT cycle for the next round of PDT to generate 1 O2 . The working principle and phototherapy efficacy are preliminarily demonstrated in living cells and tumor‐bearing mice, respectively. Abstract : A photosensitive nanodrug An‐NP that allows sustained 1 O2 generation and sufficient oxygen supply during the entire phototherapy is engineered by alternatively applying PDT and PTT controlled by dual light. In PDT, An‐NP generates 1 O2 with extra 1 O2 being trapped via the conversion into EPO‐NP. In subsequent PTT, EPO‐NP undergoes thermolysis to liberate the captured 1 O2 and regenerates An‐NP.